After the facts: Producing, using and contesting knowledge in two spatial-environmental conflicts in the Netherlands. (May 2021) - Roth, Dik; Köhne, Michiel; Rasch, Elisabet Dueholm; Winnubst, Madelinde
While the problematic role of knowledge in controversial policy processes is widely acknowledged, relatively little is known about how protesting citizen groups involved in such controversies construct, mobilize and use knowledge. This article explores these issues in two conflicts about planned interventions in the Netherlands. The first case, about energy policies, concerns protests against plans for shale gas extraction. In the second case, concerning flood risk management, citizens organized protests against a planned 'bypass' of the River Waal. To better understand the role of citizen groups as knowledge actors, we analyse how these groups organized and strategized their protests and produced, used and contested knowledge to claim voice in decision-making. The study shows the key role of citizen groups as knowledge actors in contested planning processes, and of their knowledge strategies in internally divided communities. It also shows the importance of the source and type of knowledge and how it is constructed, mobilized and used in various stages of resistance against policy plans.